Galois Covers, Grothendieck-Teichmüller Theory and Dessins d'Enfants Interactions between Geometry, Topology, Number Theory and Algebra, Leicester, UK, June 2018 /: Interactions between Geometry, Topology, Number Theory and Algebra, Leicester, UK, June 2018. (2020) - Unknown
No abstract available